2013
DOI: 10.5713/ajas.2012.12671
|View full text |Cite
|
Sign up to set email alerts
|

Guava (<italic>Psidium guajava</italic> L.) Powder as an Antioxidant Dietary Fibre in Sheep Meat Nuggets

Abstract: This study was conducted to explore the antioxidant potential and functional value of guava (Psidium guajava L.) powder in muscle foods. Guava powder was used as a source of antioxidant dietary fibre in sheep meat nuggets at two different levels i.e., 0.5% (Treatment I) and 1.0% (Treatment II) and its effect was evaluated against control. Guava powder is rich in dietary fibre (43.21%), phenolics (44.04 mg GAE/g) and possesses good radical scavenging activity as well as reducing power. Incorporation of guava po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
52
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 54 publications
34
52
1
2
Order By: Relevance
“…Similar decrease in the pH was reported by Verma et al (2013) in sheep meat nuggets on incorporation of guava powder and Banerjee et al (2012) in goat meat nuggets on incorporation of broccoli powder extract. Verma et al (2012a) and (2012b) also observed a decrease in pH of chicken nuggets incorporated with bottle gourd and chickpea hull flour, respectively.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar decrease in the pH was reported by Verma et al (2013) in sheep meat nuggets on incorporation of guava powder and Banerjee et al (2012) in goat meat nuggets on incorporation of broccoli powder extract. Verma et al (2012a) and (2012b) also observed a decrease in pH of chicken nuggets incorporated with bottle gourd and chickpea hull flour, respectively.…”
Section: Resultssupporting
confidence: 86%
“…Verma et al (2013) also observed a decrease in the fat content of sheep meat nuggets on incorporation of guava powder. Suradkar et al (2013), Verma et al (2012a) and (2012b) also reported similar results in different meat products.…”
Section: Resultsmentioning
confidence: 90%
“…Similar decrease in the pH was also reported by Verma et al (2013) in sheep meat nuggets with the incorporation of guava powder and Banerjee et al (2012) in goat meat nuggets with the incorporation of broccoli powder extract. This is however, in contrast to Aytul et al (2008) who observed no significant change in the pH of the products treated with olive leaf extract.…”
Section: Phsupporting
confidence: 84%
“…Decrease in a phenolic content of patties might be due to the heating of the patties during the sensory evaluation at three days interval and heating leads to loss or denaturation of the some phenolic content in patties. The Naveena et al, (2008) in cooked chicken patties; Devatkal et al, (2010b) in goat meat patties; Verma et al, (2013) in sheep meat nuggets and Serdaroglu et al, (2015) in raw beef pattiesfound similar results with present findings. The higher level of phenolics may indicate patties is nutritionally enhanced due to the fruit extract and seed coat extract that was added (Leheska et al, 2006).…”
Section: Total Phenolic Contentsupporting
confidence: 91%